High Prevalence of Hypercholesterolemia and Central Obesity among Medical Faculty Staff: A Cross-Sectional Study at Universitas Sebelas Maret - Victoria Husadani Permata Sari; Danang Wahansa Sugiarto; Arsita Eka Prasetyawati; Lukman Aryoseto (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: Hypercholesterolemia and central obesity are major modifiable risk factors for cardiovascular disease. Underdiagnosis and low awareness persist regarding these conditions, even among populations with presumed high health literacy, such as staff at medical education institutions. This study aimed to determine the prevalence of hypercholesterolemia and central obesity in staff at the Faculty of Medicine, Universitas Sebelas Maret (FK UNS), and assess the level of individual awareness regarding these conditions.Methods: A cross-sectional study was conducted using data from Posbindu (Integrated Development Post for Non-Communicable Diseases) activities in August 2024, April 2025, and May 2025. A total of 293 participants underwent anthropometric and cholesterol screening. Waist circumference defined central obesity, and capillary blood tests measured cholesterol levels. Questionnaires are used to capture dietary habits, cholesterol history and awareness. Descriptive statistics were used, along with a Pearson’s chi-square test, to assess associations. Results: The prevalence of hypercholesterolemia was 52%, with higher rates observed among females (72%) compared to males (28%). Central obesity was present in 46% of participants, more frequent in females (52%) than males (44%). Only 22% were aware of their cholesterol status prior to screening. A significant association was found between awareness and cholesterol status (p-value = 0.016).Conclusion: High prevalence rates of hypercholesterolemia and central obesity, combined with low awareness, highlight a critical gap between health literacy and preventive action within staff medical education institutions. Strengthening institutional health programs with integrated and behavior-focused health interventions may enhance risk awareness and promote healthier lifestyles.